Analisis Transparansi dan Akuntabilitas dalam Pengelolaan Keuangan Desa di Desa Mekarlaksana Kabupaten Bandung - Clara Fatiha Dewanti; I Gusti Ketut Agung Ulupui; Petrolis Nusa Perdana (Indo Publishing, 2026)
This study analyzes transparency and accountability in village financial management. The background of this study is the continued problems in the implementation of transparency and accountability in village financial management, such as limited access to public information and suboptimal presentation of financial reports to the public. The purpose of this study is to understand the importance of implementing transparency and accountability in village financial management as an effort to realize good governance and prevent budget misuse. This study uses a qualitative approach with a case study method. Primary data were collected through interviews with informants, namely the Village Head, Village Secretary, Finance Officer, Village Consultative Body and Village Community. Secondary data were obtained from documents owned by the Mekarlaksana Village Government. The data in this study were analyzed by referring to the provisions contained in the Regulation of the Minister of Home Affairs Number 20 of 2018. The results of the study indicate that Mekarlaksana Village has implemented the principles of village financial management in accordance with the Regulation of the Minister of Home Affairs Number 20 of 2018, but its implementation has not been optimal in several aspects. This demonstrates the need for improvements in village financial management to comply with the provisions stipulated in Minister of Home Affairs Regulation Number 20 of 2018.